2006
DOI: 10.1002/hbm.20263
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different cortical connectivity estimators for high‐resolution EEG recordings

Abstract: Abstract:The aim of this work is to characterize quantitatively the performance of a body of techniques in the frequency domain for the estimation of cortical connectivity from high-resolution EEG recordings in different operative conditions commonly encountered in practice. Connectivity pattern estimators investigated are the Directed Transfer Function (DTF), its modification known as direct DTF (dDTF) and the Partial Directed Coherence (PDC). Predefined patterns of cortical connectivity were simulated and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
277
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 337 publications
(285 citation statements)
references
References 69 publications
(100 reference statements)
7
277
0
1
Order By: Relevance
“…Although PDC has proved to be an accurate tool for the detection of direct connectivities, both in cases of coupled oscillators (Baccalá and Sameshima 2001;Winterhalder et al 2005;Gourévitch et al 2006;Schelter et al 2006a) or simple neuronal models of interconnected neurons (Sameshima and Baccalá 1999;Kamiński et al 2001;Astolfi et al 2007), it has been shown that large differences in the variances of the modeled time series can yield distortions in the resulting PDC values (Winterhalder et al 2005;Baccala et al 2007). For example, a set of three uncorrelated white noise processes, where two of them have much larger variance than the third, will produce a distorted connectivity profile, since PDC wrongly detects connections from the low-variance process to the other two (Winterhalder et al 2005).…”
Section: Partial Directed Coherencementioning
confidence: 99%
“…Although PDC has proved to be an accurate tool for the detection of direct connectivities, both in cases of coupled oscillators (Baccalá and Sameshima 2001;Winterhalder et al 2005;Gourévitch et al 2006;Schelter et al 2006a) or simple neuronal models of interconnected neurons (Sameshima and Baccalá 1999;Kamiński et al 2001;Astolfi et al 2007), it has been shown that large differences in the variances of the modeled time series can yield distortions in the resulting PDC values (Winterhalder et al 2005;Baccala et al 2007). For example, a set of three uncorrelated white noise processes, where two of them have much larger variance than the third, will produce a distorted connectivity profile, since PDC wrongly detects connections from the low-variance process to the other two (Winterhalder et al 2005).…”
Section: Partial Directed Coherencementioning
confidence: 99%
“…Thus, studies using these methods may be subject to a mismatch between the system properties represented by the measures and the properties of interest to the investigator. Despite the clear fundamental differences in how these and other causality measures are defined, these methods are often discussed as interchangeable alternatives or referred to generically as "Granger causality" (35,44,45), making it even more difficult to interpret studies using these methods.…”
Section: Resultsmentioning
confidence: 99%
“…For each subject, the electrodes disposition on the scalp surface was generated through a nonlinear minimization procedure [12]. The cortical model consists of about 5,000 dipoles uniformly disposed on the cortical surface and the estimation of the current density strength for each dipole was obtained by solving the electromagnetic linear inverse problem according to the techniques described in previous papers [13][14][15]. For each experimental subject, the statistical significance of the Power Spectral Density (PSD) values elicited during the observation of the TV commercials was then measured against the activity evaluated during the observation of the documentary.…”
Section: Cerebral Recordings and Signal Processingmentioning
confidence: 99%
“…The system also includes the measurement noise n, assumed to be normally distributed [13][14][15][16].…”
Section: Estimation Of Cortical Activity the Solution Of The Followimentioning
confidence: 99%